Frauen-Portraits - Ramshorn, Carl, 1812-1887 (Gerritsen collection of women's history ;, 1873)
A collection of biographical essays on such women as Maria Theresia, Louise of Prussia, Mary Stuart, Queen Elizabeth I., Joan of Arc, and Marie Antoinette, among others.